Inside Smartgeometry : expanding the architectural possibilities of computational design - Peters, Brady; Peters, Terri (Chichester, West Sussex, UK : Wiley, 2013)
Smartgeometry (SG) is a key influence on the architectural community who explore creative computational methods for the design of buildings. An informal international network of practitioners and researchers, the group meets annually to experiment with new technologies and collaborate to develop digital design techniques. When SG was founded in 2001 by London-based architects and friends Hugh Whitehead (Foster + Partners), J Parrish (AECOM) and Lars Hesselgren (PLP), there was little in the way of parametric tools for architecture. SG was founded to encourage the development, discussion and
Introduction / Brady Peters, Terri Peters -- The Origins of Smartgeometry / Hugh Whitehead, Lars Hesselgren, J Parrish -- First Build Your Tools / Robert Aish -- Parametric Evolution / Branko Kolarevic -- Matrix Architecture / Jenny E Sabin -- Metrics of Human Experience / Roly Hudson, Michael Westlake -- Interacting with the Model / Neil Katz, Bess Krietemeyer, Tobias Schwinn -- Responsive Design: Towards an Ecology of Objects and People / Andre Chaszar, Anton Savov, Peter Liebsch, Sascha Bohnenberger -- Design Flow and Tool Flux / Robert Woodbury -- The Sound of Smartgeometry / Brady Peters -- Design Exploration and Steering of Design / Axel Kilian -- Geometry: How Smart Do You Have to Be? / Chris Williams -- Generative Components and Smartgeometry: Situated Software Development / Volker Mueller, Makai Smith -- From Descriptive Geometry to Smartgeometry: First Steps Towards Digital Architecture / Mark Burry -- Exploring Human-Computer Interaction in Design Process / Flora Salim, Przemek Jaworski -- Designing Intelligence: DIY Robotics for Responsive Environments / Nick Puckett -- Encoding Design / Fabian Scheurer -- Working Prototypes, Creating Knowledge / Shane Burger, Xavier De Kestelier -- Mind the Gap: Case Stories of Exchange -- Designing Robotic Assemblies / Tobias Bonwetsch -- The Practice of Smartgeometry / Hugh Whitehead -- Digital Crafting: Performative Thinking for Material Design / Mette Ramsgard Thomsen, Martin Tamke -- Design Robotics: New Strategies for Material System Research / Martin Bechthold -- Contributor Biographies.
Description based on print version record.
Keywords: Smartgeometry; Architecture and technology -- Great Britain; Architectural practice -- Great Britain; Architectural design -- Data processing; Engineering; ARCHITECTURE / Adaptive Reuse & Renovation; ARCHITECTURE / Buildings / Landmarks & Monuments; ARCHITECTURE / Professional Practice; ARCHITECTURE / Reference; Electronic books